Clinicians in court : a guide to subpoenas, depositions, testifying, and everything else you need to know - Barsky, Allan Edward (Guilford Press, 2002)
Mental health and human service professionals are often called on to give evidence or expert testimony in a range of circumstances, including family law and child welfare trials, mental health hearings, malpractice lawsuits, criminal trials, government hearings, and private arbitration. Interacting with the legal system poses many potential challenges, but adequate preparation and a basic understanding of legal processes and terminology can make the experience a more positive one. This volume provides practical information to help clinicians from any background understand their role in legal proceedings, and participate effectively, ethically, and with minimal stress. It demonstrates how to respond to subpoenas or contacts from lawyer; how to prepare for particular court actions; and how to ensure that all documentation is complete and legally admissible, and confidentiality requirements are met. A resource for therapists and counselors in any setting, this guide will also be of interest to agency administrators and policymakers, as well as legal practitioners seeking to educate potential witnesses. It will also serve as a text in professional seminars and training courses and in graduate-level courses on forensic mental health practice and mental health law.